Inside Cover: Multiple Conformations of the Loop Region Confers Heat‐Resistance on SsArd1, a Thermophilic NatA (ChemBioChem 3/2016). Issue 3 (3rd February 2016) - Chang, Yu‐Yung; Hsu, Chun‐Hua
Abstract : The inside cover picture shows the secret of heat tolerance of a thermophile: Nα‐acetyltransferase SsArd1 hides in its unique loop, which is extended and longer than the corresponding region in mesophilic homologues. Evidence demonstrates that multiple conformations of the extended loop contribute to protein thermostability; they are formed through the plastic hydrogen‐bond network mainly at Ser75 and Ser82. More information can be found in the communication by Y.‐Y. Chang and C.‐H. Hsu onpage 214 in Issue 3, 2016 (DOI:10.1002/cbic.201500568 ).